Effect evaluation, prediction and response strategy analysis of China’s birth policy adjustment - Wei Wang; Yalan Mo; Yanxi Kuang (PLoS ONE, 2025)
In recent years, in order to cope with the increasing trend of population aging, the Chinese government has constantly adjusted the family planning policy, continuously tracked and evaluated the actual effect of the birth policy adjustment, and the prediction and analysis of future births have important theoretical value and practical significance.The adjustment of the birth policy is of great significance for achieving long-term balanced population development. This paper assesses the net effect of fertility policy adjustments on Chinas birth and fertility rates by constructing a DID model using panel data collected from 31 provinces, autonomous regions and municipalities over the period 2005-2021. The study shows that the fertility policy adjustment does not significantly increase the birth and fertility rates in China, and the findings are confirmed by robustness tests using various methods. Heterogeneity analysis shows that the implementation of the comprehensive two-child policy is more pronounced in the central region. Further, a mechanistic and causal analysis reveals that fertility policy changes did not significantly increase peoples willingness to have children, nor did they affect many other factors that influence households fertility decisions. Finally, a GM (1, 1) grey forecast model is used to forecast the births in each province and municipality in the next five years, and it is concluded that the births in China will continue to show a declining trend. This paper argues that a supportive policy system for fertility should be established, public childcare and elderly care services should be optimised, and a favourable fertility climate and conditions should be created in order to improve fertility levels in China.